MOTIF DAN KEPUASAN REMAJA DENPASAR MENONTON KONTEN VIDEO @haipuja MELALUI INSTAGRAM (E-Jurnal Medium, 2022)
Instagram is a social network-based platform that is used to share content in the form of photos or videos. Video content is a content or information on a media in the form of moving images containing text or audio arranged in digital form. In consuming media, media users are based on a certain motive. This study aims to find out what the underlying motives for Denpasar teenagers are to watch @haipuja's video content via Instagram and how satisfaction is obtained by Denpasar teenagers from watching @haipuja's video content via Instagram. The research location was chosen in Denpasar City because the number of internet users is the highest in Bali Province with the research subjects being Denpasar teenagers aged 13-24 years. The theory used in this study is the Uses and Gratification theory using the concept of motives from Denis McQuail which consists of information motives, personal identity motives, integration and social interaction motives, and entertainment motives. The research method used is descriptive quantitative type. Data were collected by distributing questionnaires using a Likert scale. The results showed that the satisfied motives were information motives, personal identity motives, and entertainment motives, while the unsatisfied motives were integration and social interaction motives. So, it can be concluded that Denpasar teen watch @haipuja's video content to seek information, find out the latest issues, get to know themselves, look for interesting trends, seek entertainment and improve the mood, while related to moral messages and teachings of kindness and sensitivity to the surrounding environment, it is not very easy to find by a Denpasar teenager in @haipuja's video content. Keywords: Motives, Satisfaction, Teen, Instagram